Consistência na análise de sinal EMG de superfície nos membros inferiores em diferentes contramovimentos verticais - Carlos Rodrigues (2017)
Aim: Consistency assessment of the analysis and results of different EMG surface signal from lower limb strategic muscle groups during vertical countermovement (CM) for maximum vertical impulse jump (MVIJ). Methods: The sample group is composed by n=6 sports and physical education degree students, without any specific training or ability. Subjects with ages (21,5±1,4) years old were weighted (76,7±6,7) kg and measured their height (1,79±0,05) m. Skintact F55 Aqua-Wet electrodes were disposed according to SENIAN convention on bipolar configuration at lower limb selected muscles rectus femoris (RF), vastus medialis (VM), vastus lateralis (VL), medial and lateral gastrocnemius (MG/LG). Each subject performed a total of 3 trials for each MVIJ, without CM (SJ - Squat Jump), with long CM (CMJ - Counter Movement Jump) and with short CM (DJ - Drop Jump). EMG raw signal were rectified, filtered and linear envelope obtained for linear correlation (CR) to detect synergistic, agonistic and antagonistic activity, principal component analysis (PCA) for detection of uncorrelated components explaining maximum variability, as well as normalized cross-correlation (NCCR) for detection of maximum correlation and time delay.Results: Correlations of EMG linear envelops lead to detection of higher co-activities at DJ when compared to SJ and higher co-activities at SJ when compared to CMJ with higher synergies at DJ in relation to SJ and CMJ, both presenting loops associated to EMG phase delay. NCCR of EMG linear envelops also pointed to higher co-activities at DJ when compared to SJ, both with higher co-activities when compared to CMJ. Principal component analysis detected 1 component explaining 92.2% variability of considered EMG at DJ, 90.6% at SJ and 78.7% at CMJ, with second component explaining 4.9% variability at DJ, 6.7% at SJ and 15.3% at CMJ. Conclusions: Linear correlation (CR), normalized cross-correlation (NCCR) and principal component analysis (PCA) presented consistent results concerning EMG signal analysis of selected muscle groups during considered countermovement.